Two new species and two new varieties of Aspidistra (Asparagaceae, Convallarioideae) from the Central Highlands of Vietnam - Averyanov, Leonid V.; Nguyen, van Canh; Nuraliev, Maxim S.; Vislobokov, Nikolay A.; Maisak, Tatiana V.; Thuy, Nhan Tran Thi; Quang, Cuong Truong; Krupkina, Ludmila I. (Phytotaxa, 2025)
The paper presents new data on the diversity of Aspidistra in Vietnam obtained during the fieldwork of 2025 in the Central Highlands (also known as Tay Nguyen Plateau). It includes four taxa new to science, viz. the species A. microstyla and A. nguyenii and the varieties A. brachypetala var. danii and A. mirostigma var. haui. Aspidistra brachypetala is reported here as a new species record for Vietnam. For each taxon, information on morphology, ecology, phenology, conservation status and distribution is presented, as well as relevant taxonomic notes and analytical photographic illustrations.